Deep colonic endoscopic submucosal dissection using a modified clip and snare method incorporating a pre-looping technique. (23rd January 2015) - Ota, Ryosuke; Doyama, Hisashi; Tsuji, Kunihiro; Yamada, Shinya
Abstract : Endoscopic submucosal dissection (ESD) is more difficult to perform for colorectal cancer than for early gastric cancer. The use of traction to facilitate direct submucosal layer visualisation is promising in reducing the procedure's time and complication rate. We report a case in which deep colonic ESD was performed with a modified clip and snare method. A 57-year-old man was admitted for ESD of a laterally spreading caecal lesion 25 mm in size (classified as LST-GM) that had been found on colonoscopy. The clip and snare method was previously developed for ESD of gastric cancer; we improved on this method and applied our pre-looping technique in the deep colon. The procedure lasted 40 min and was without complications. Our pre-looping technique represents a modification of the clip and snare method, enabling its performance in the deep colon. We expect that our technique will be applicable to colorectal tumours.